Children’s emotion regulation strategies in facing the Volatile, Uncertain, Complex, and Ambiguous (VUCA) World: A systematic narrative review - Fatin Syamilah Che Yob; Afiq Azri Mohd Ghani; Lim Seong Pek; Rita Wong Mee Mee; Md Rosli Ismail; Uzzairah Nabilah Ahmad Tazli; Tengku Shahrom Tengku Shahdan (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Despite an increasing number of studies conducted on emotion regulation strategies, there is, however, a limited resource that acknowledges it as a whole due to an inclination towards children’s well-being development. Thus, this research aims to produce a synthesis review of children’s emotion regulation strategies in preparation to encounter a volatile, uncertain, complex, ambiguous (VUCA) world. The articles for systematic narrative review were retrieved through a rigorous database search from 2015 until current. Thirteen relevant articles were retrieved through a systematic search that concentrated on children’s emotion regulation strategies. Five different families of emotion regulation strategies were identified from finalised articles including: (1) situation selection; (2) situation modification; (3) attentional deployment; (4) cognitive change; and (5) response modulation. The findings from the articles were synthesised into a literature matrix and added as supporting statements when all five strategies were further discussed. The systematic narrative review indicated that children from various age groups used the five emotion regulation strategies differently. The situational context was also considered when children used the strategies, as the were they were studies focused on different social contextual factors. Besides, in certain age groups, children are keen to use one of the emotion regulation strategies frequently.